Decadal Dynamics of the CO2 System and Associated Ocean Acidification in Coastal Ecosystems of the North East Atlantic Ocean - Gac, Jean-Philippe; Marrec, Pierre; Cariou, Thierry; Grosstefan, Emilie; Macé, Éric; Rimmelin-Maury, Peggy; Vernet, Marc; Bozec, Yann (Frontiers in Marine Science, 2021)
Weekly and bi-monthly carbonate system parameters and ancillary data were collected from 2008 to 2020 in three coastal ecosystems of the southern Western English Channel (sWEC) (SOMLIT-pier and SOMLIT-offshore) and Bay of Brest (SOMLIT-Brest) located in the North East Atlantic Ocean. The main drivers of seasonal and interannual partial pressure of CO2 (pCO2) and dissolved inorganic carbon (DIC) variabilities were the net ecosystem production (NEP) and thermodynamics. Differences were observed between stations, with a higher biological influence on pCO2 and DIC in the near-shore ecosystems, driven by both benthic and pelagic communities. The impact of riverine inputs on DIC dynamics was more pronounced at SOMLIT-Brest (7%) than at SOMLIT-pier (3%) and SOMLIT-offshore (<1%). These three ecosystems acted as a weak source of CO2 to the atmosphere of 0.18 ± 0.10, 0.11 ± 0.12, and 0.39 ± 0.08 mol m–2 year–1, respectively. Interannually, air-sea CO2 fluxes (FCO2) variability was low at SOMLIT-offshore and SOMLIT-pier, whereas SOMLIT-Brest occasionally switched to weak annual sinks of atmospheric CO2, driven by enhanced spring NEP compared to annual means. Over the 2008–2018 period, monthly total alkalinity (TA) and DIC anomalies were characterized by significant positive trends (p-values < 0.001), from 0.49 ± 0.20 to 2.21 ± 0.39 μmol kg−1 year−1 for TA, and from 1.93 ± 0.28 to 2.98 ± 0.39 μmol kg–1 year–1 for DIC. These trends were associated with significant increases of calculated seawater pCO2, ranging from +2.95 ± 1.04 to 3.52 ± 0.47 μatm year–1, and strong reductions of calculated pHin situ, with a mean pHin situ decrease of 0.0028 year–1. This ocean acidification (OA) was driven by atmospheric CO2 forcing (57–66%), Sea surface temperature (SST) increase (31–37%), and changes in salinity (2–5%). Additional pHin situ data extended these observed trends to the 2008–2020 period and indicated an acceleration of OA, reflected by a mean pHin situ decrease of 0.0046 year–1 in the sWEC for that period. Further observations over the 1998–2020 period revealed that the climatic indices North Atlantic Oscillation (NAO) and Atlantic Multidecadal Variability (AMV) were linked to trends of SST, with cooling during 1998–2010 and warming during 2010–2020, which might have impacted OA trends at our coastal stations. These results suggested large temporal variability of OA in coastal ecosystems of the sWEC and underlined the necessity to maintain high-resolution and long-term observations of carbonate parameters in coastal ecosystems.